Electrospun Nanostructures for High Performance Chemiresistive and Optical Sensors. Issue 8 (19th May 2017) - Choi, Seon‐Jin; Persano, Luana; Camposeo, Andrea; Jang, Ji‐Soo; Koo, Won‐Tae; Kim, Sang‐Joon; Cho, Hee‐Jin; Kim, Il‐Doo; Pisignano, Dario
Abstract : This comprehensive review provides recent progresses of chemical sensors based on chemiresistive‐type semiconductor metal oxides and optical‐type nanomaterials exploiting absorption and emission properties. In particular, the authors focus on the diverse 1D nanofibrous structures synthesized by electrospinning technique for application in chemical sensor. Abstract : Chemical sensors have been essential components in recent years due to the gathering attention in environmental monitoring and healthcare. In this review, the authors comprehensively highlight recent progresses on the 1D chemiresistive‐type sensors based on semiconductor metal oxides (SMOs) and optical‐type sensors, which are prepared by electrospinning technique. In the part of chemiresistive‐type sensors, diverse synthesis techniques for 1D SMO nanofibrous structure are presented with controlled microstructure and surface morphology. In addition, unique functionalization routes of emerging nanocatalysts encapsulated by bio‐inspired templates are described for the next generation catalyst on the 1D SMO nanofibers (NFs). For the optical‐type sensors, new classes of 1D NFs employing specific absorption and emission properties are introduced. In particular, diverse 1D NF‐based colorimetric and fluorescence sensors as well as Raman and surface‐enhanced Raman scattering sensors are covered in the view point of material preparation and optical sensing properties. Finally, the authors prospect future research directions to overcome current limitations and challenges to achieve high performance chemical sensors.